2006
DOI: 10.4049/jimmunol.177.5.3178
|View full text |Cite
|
Sign up to set email alerts
|

Murine Vβ3+ and Vβ7+ T Cell Subsets Are Specific Targets for the HERV-K18 Env Superantigen

Abstract: Superantigens are a class of proteins that are derived from microorganisms and have the unique characteristic of stimulating T cells in a TCR Vβ-specific manner, causing massive T cell proliferation and immune deregulation. For this reason, superantigens have been implicated in the development of multiple diseases. We have previously identified and cloned an EBV-associated superantigen, human endogenous retrovirus (HERV)-K18 envelope protein (Env). This superantigen is transactivated upon IFN-α treatment and E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…We further confirmed that HERV-K18 env is inducible in our double transgenic mice by anti-IgM treatment of the purified B cells (Fig. 2E) (26).…”
Section: Generation Of Hcd21/herv-k18 Double Transgenic Micesupporting
confidence: 68%
See 1 more Smart Citation
“…We further confirmed that HERV-K18 env is inducible in our double transgenic mice by anti-IgM treatment of the purified B cells (Fig. 2E) (26).…”
Section: Generation Of Hcd21/herv-k18 Double Transgenic Micesupporting
confidence: 68%
“…Thus, we produced double transgenic mice expressing hCD21 and HERV-K18 from bacteria artificial chromosomes (BACs). The HERV-K18 transgenic mice have been described elsewhere (26). To ensure that the hCD21 transgene is expressed from its native human regulatory elements and promoters, we selected a BAC, RP11-35C1, that contains hCD21 flanked by complement receptor 1 (CD35) and a hypothetical protein for injection into fertilized FVB eggs.…”
Section: Generation Of Hcd21/herv-k18 Double Transgenic Micementioning
confidence: 99%
“…In addition, studies on the mechanism by which EBV stimulates HERV-K18 has implicated the EBV surface glycoprotein gp350 via signaling through CD21 (219) and the latent EBV proteins LMP-1 and LMP2A (471). HERV-K18 expression is also induced in B cells by immunoglobulin M cross-linking of CD40 on the cell surface (476). Therefore, current evidence now provides a more persuasive argument that the HERV-K18 SAg activity is genuine.…”
Section: Herv-k and Melanomamentioning
confidence: 93%
“…However, more recent work in mice transgenic for the HERV-K18 genomic locus has shown that murine V␤3 and V␤7 T-lymphocyte subsets are activated by HERV-K18 SAg in vivo (476). In addition, studies on the mechanism by which EBV stimulates HERV-K18 has implicated the EBV surface glycoprotein gp350 via signaling through CD21 (219) and the latent EBV proteins LMP-1 and LMP2A (471).…”
Section: Herv-k and Melanomamentioning
confidence: 99%
See 1 more Smart Citation